(untitled) (Experimental biology, 2015)
This paper presents the results of players to explore the use of functional loads. The proposed system of training players in the weekly cycle with a change in the intensity and form of executable load exercises allowing for improved athletic performance coupled with a high level of functional state of the major functional systems of the body, cardio-vascular. The results obtained can be used to study the construction of the training process for the preparation of professional athletes, for athletes and enthusiasts.